Service oriented architecture and advancement of maintenance management information systems: a review - Shareghi, Masood; Abdul Aziz, Faieza (Academic Journals, 2011)
Global competitive environment among enterprises requires efficient business interactions with external and internal entities in companies. Maintenance management systems are one of the critical business units in companies that play a key role in reducing the downtime of machinery and equipment. Therefore, the maintenance management interactions need to be optimized. The new era of information technology lead to apply information system in wide extends in maintenance management. Maintenance management systems have been improved by information technology to facilitate the accessibility, storing, and retrieving information. This article reviews the recent trends in maintenance management information systems and various maintenance applications. Applying service oriented architecture (SOA) and e-maintenance strategy in industries shows that integration trend in maintenance management information technology grows rapidly. Suggestion has been made on classifications of services which can be handled in an SOA enabled maintenance management system.